2011
DOI: 10.1111/j.1365-2389.2010.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-optode measurements of ammonium distribution in soil after different manure amendments

Abstract: The choice of manure application technique can affect both the spatial distribution of ammonium in soil and net nitrogen (N) mineralization, and thereby N availability to crops. In this study we compared net N mineralization and spatial ammonium distribution after different degrees of incorporation of solid chicken manure and cattle slurry into soil. Ammonium-specific fluorescing optodes were assembled with manure applied to soil in closed chambers and the spatial distribution of ammonium in different treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Baitilwake et al (2012) found greater immobilization and nitrification after soil incorporation than surface application of chicken and cattle manure. However, Delin and Strömberg (2011) did not find any differences in net mineralization of nitrogen between surfaceapplied and incorporated chicken manure and cattle slurry, as long as the manure was kept in concentrated lumps, although when the manure was mixed with a larger soil volume both net immobilization and nitrification increased.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Baitilwake et al (2012) found greater immobilization and nitrification after soil incorporation than surface application of chicken and cattle manure. However, Delin and Strömberg (2011) did not find any differences in net mineralization of nitrogen between surfaceapplied and incorporated chicken manure and cattle slurry, as long as the manure was kept in concentrated lumps, although when the manure was mixed with a larger soil volume both net immobilization and nitrification increased.…”
Section: Introductionmentioning
confidence: 67%
“…Band application would probably still be as successful as in 25 cm spacing, as long as pellets are not put together with the seeds. The benefit could be because of more efficient incorporation and lower immobilization (Sørensen and Jensen, 1995;Delin and Strömberg, 2011).…”
Section: Crop Row Spacingmentioning
confidence: 99%
“…The HPTS(TOA) ion pair, immobilized in ethyl cellulose, is to date the only indicator reported to be used for planar optode imaging of pCO 2 [20,72]. The polarity-sensitive fluorescent indicator merocyanine 540 (MC540) has been developed and applied for NH 4 + imaging [74,[132][133][134]. The sensing system relies on a co-extraction technique [135], where the sensor matrix is based on a two phase system, containing a hydrogel (NH 80/92) and non-polar ether emulsion droplets.…”
Section: Pco 2 Nh 4 + and Sulphide Indicatorsmentioning
confidence: 99%
“…Quantification of the NH 4 + concentration is made through a dual-excitation dual-emission ratiometric imaging approach [132]. Using timecorrelated pixel-by-pixel calibration [74,127] this sensor was stable for up to 10 days at concentrations from 0 to 500 mmol L À1 [74,134].…”
Section: Pco 2 Nh 4 + and Sulphide Indicatorsmentioning
confidence: 99%
“…Also the analytical performance such as sensitivity, limit of detection (LOD), and expected operational lifetime were calculated for each pixel and presented as statistical images [9]. After improvements of the infinity corrected imaging system as well as a high throughput macro imaging techniques were developed [10], the technique was ready for research applications such as studying ammonium uptake close to roots [11], and multiple fertilizer release studies (using a high throughput imaging system) in different soils [12] over long time periods up to 11 days.…”
Section: N Strömberg 136mentioning
confidence: 99%